Design of transport services as mobility as a service with hyperledger blockchain (A) - Wong, Weng Soon (Nanyang Technological University, 2022)
The concept of Mobility as a Service has the potential to serve the needs of the commuters more effectively. With the technology of blockchain, we would like to see if it is feasible to produce proof-of-concept with MaaS. The reason to use blockchain was simply to allow more integration among different organisations to better serve the commuters. The organisations may include the government of the country, private sector companies that support transport services and maintenance services. This prevents any single company to become the dominant market leader which may lead to a lack of competition in the market. The use of blockchain technology which offers decentralised and transparency solutions will help to resolve issues pertaining to it. For this project, we would be using an airline consortium as an example to show the proof of concept.